Ideas and Options in English for Specific Purposes - Helen Basturkmen
Part I introduces the book's approach to description of ESP and the framework used to investigate it. Part II examines ideas of language, learning, and teaching in ESP. Recognizing that ESP is taught in many different countries and contexts, the author draws on a wide range of examples of teaching practice and research from around the world and from different branches of ESP, including English for Academic Purposes, English for Professional Purposes, and English for Vocational Purposes. From Chapter 3 onward, each chapter includes Questions for Discussion and Projects, to encourage readers to research and analyze the practices of ESP in their own contexts and to consider the ideas they draw on in their own teaching.